Effect of red plum on quality characteristics of banana milk smoothies - Kumar, Brijesh; Singh, VP; Pathak, Vikas; Verma, Akhilesh K (Indian Journal of Dairy Science, 2021)
The present study was carried out to enhance the functional quality of milk smoothies. Experiments were conducted on various formulations of smoothies using banana (T1 without plum) and red plum in different proportions (75:25 (T2), 50:50(T3), and 25:75 (T4)) along with Sahiwal cows milk. Results revealed that physico-chemical quality characteristics of control (T1 banana-based smoothie) and smoothie replaced with red plum differ significantly (P